The Gospel According to Star Wars: Faith, Hope, and the Force - Zelenka, Michael (Catholic Education: A Journal of Inquiry and Practice, 2010)
Review of John C. McDowell's book The Gospel According to Star Wars: Faith, Hope, and the Force.